Study on drilling parameters using high speed steel (HSS) and cobalt tools cutter / Fadhirul Azreen Hishamuddin. - Hishamuddin, Fadhirul Azreen (2009)
This study presents experimental observations of the influence of the machining parameter on the surface roughness obtained from drilling operation. A plan of experiment, based on the Taguchi approach, had been applied to optimize three machining parameters for two types of cutting tool which are High Speed Steel (HSS) and Cobalt tool. Through this method, the use of orthogonal array, the signal to noise (S/N) ratio and the analysis of variance (ANOVA) were utilized to identify optimal machining parameters of mild steel. The machining parameters involved are cutting speed, feed rate and depth of cut which were designed in a L-9 orthogonal array.